Comments on “Coexistence of hidden chaotic attractors in a novel no-equilibrium system” (Nonlinear Dyn, doi:10.1007/s11071-016-3170-x) - Petráš, Ivo (Nonlinear Dyn, 2017)
In this comment, an enhancement of issue published in the paper “Coexistence of hidden chaotic attractors in a novel no-equilibrium system” (Nonlinear Dyn, doi:10.1007/s11071-016-3170-x) is addressed. We have shown that the proposed novel autonomous chaotic system can be extended to its fractional-order version where hidden attractors as well as other dynamical properties of the new no-equilibrium system can be observed. A created MATLAB function for the new fractional-order no-equilibrium system is also presented.